The Water Walker - Robertson, Joanne, 1960- (Second Story Press, 2017)
"This is the story of a determined Ojibwe Grandmother (Nokomis) Josephine Mandamin and her great love for Nibi (Water). Nokomis walks to raise awareness of our need to protect Nibi for future generations, and for all life on the planet. She, along with other women, men, and youth, have walked around all of the Great Lakes from the four salt waters - or oceans - all the way to Lake Superior. The water walks are full of challenges, and by her example Josephine inspires and challenges us all to take up our responsibility to protect our water and our planet for all generations. Her story is a wonderful way to talk with children about the efforts that the Ojibwe and many other Indigenous peoples give to the protection of water - the giver of life."--